HUBUNGAN PENGGUNAAN MEDIA PHET COLORADO TERHADAP PEMAHAMAN KONSEP TRANSFORMASI ENERGI PADA SISWA KELAS IV SD INPRES PERUMNAS 1 - Ismiranda; Alya, Resky; Aulia, Jesieka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between the use of PhET Colorado learning media and students' conceptual understanding of energy changes among Grade IV students at SD Inpres Perumnas 1. This study uses a quantitative approach with correlational research design. The research population consisted of 20 Grade IV students with total sampling technique. Data collection was carried out using a closed questionnaire with a Likert scale of 1–4 to measure the use of PhET Colorado media, and a multiple-choice test to measure students' conceptual understanding of energy changes. The research instrument was validated through expert judgment and tested for reliability using Cronbach's Alpha. Data analysis was conducted using the JASP application through descriptive statistical analysis, Shapiro–Wilk normality test, and Pearson Product Moment correlation test. The results showed that the data was normally distributed with a significance value of 0.130 (p > 0.05). The results of the Pearson correlation test showed a correlation coefficient value of r = 0.983 with a significance value of p < 0.001. These results indicate that there is a very strong and significant positive relationship between the use of PhET Colorado learning media and students' conceptual understanding of energy changes. Thus, PhET Colorado can be used as an interactive digital learning medium to improve students' conceptual understanding of science in elementary school, particularly on the topic of energy changes.